"Quality" assurance features in state-funded early childhood education: A policy brief. (June 2020) - Merrill, Becca; Cohen-Vogel, Lora; Little, Michael; Sadler, James; Lee, Kenya
Highlights: The federal Education Department incentivized adoption of early education features. Adoption of these "quality assurance features" is prevalent in the American states. There is scant research supporting their effectiveness in improving child outcomes. Quality Rating and Improvement Systems show the most promise among the features. Large-scale evaluations are necessary to vet the quality of these features. Abstract: Most states in the U.S. now have some form of publicly funded Pre-Kindergarten. This brief asks what they have done to ensure the quality of their programs. It does so by mapping state adoption of three popular program quality assurance features: Early Learning Standards, Kindergarten Entry Assessments, and Tiered Quality Rating and Improvement Systems. We find that all three are now widespread across the American states, despite little research on their effects. We suggest that these quality assurance features need to be subjected to rigorous evaluation tied to their effectiveness in improving student outcomes.